'Perhaps I should be working with potted plants or standing at the fish counter instead?': newly educated social workers' reflections on their first years in practice. Issue 3 (4th May 2021) - Tham, Pia; Lynch, Deborah
ABSTRACT: The present research follows twelve Swedish social work graduates over their first years in practice. The overall aim of the study was to gain insight into the journey from their social work education into the profession. This paper presents the findings of the third series of interviews after 20 months in practice and focuses on how the new practitioners reflected on their professional role and the demands of the work. Those working in statutory social services expressed dissatisfaction with the organisational culture and work practices. They cited budget cuts, the climate of managerialism and not enough time for meeting with clients. These practitioners also reflected that their social work education had not prepared them for the complex realities of practice. Changes in the professional role of social workers within the contemporary organisational and broader policy context in Sweden and the importance of supporting the development of professional expertise in the social work journey are discussed.